2018
DOI: 10.1007/s00702-018-1901-5
|View full text |Cite
|
Sign up to set email alerts
|

Impaired finger dexterity and nigrostriatal dopamine loss in Parkinson’s disease

Abstract: Impaired finger dexterity occurs in Parkinson's disease (PD) and has been considered a limb-kinetic apraxia associated with primary sensory cortical dysfunction. To study the role of nigrostriatal dopamine loss and elementary parkinsonian motor deficits in impaired finger dexterity of PD. Thirty-two right-handed untreated PD patients and 30 right-handed healthy controls were included. All patients underwent [F] FP-CIT positron emission tomography studies. We examined the associations among unilateral coin rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…We found that most participants without PD had normal or unimpaired motor aptitude levels, while those with PD were more likely to have deficits in all areas than participants without PD, but mostly showed normal Perceptive aptitude. Although our findings were generally consistent with prior observations from other studies (Keloth et al, 2019;Lazarotto et al, 2020;Lee et al, 2018;Stegemöller et al, 2019;Stuart et al, 2019;Xu et al, 2018) our use of the MSOA permitted greater specification in describing motor aptitude differences of older adults with and without PD. Furthermore, participant gender and age group were associated with these motor aptitude outcomes, regardless of the presence or absence of PD.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that most participants without PD had normal or unimpaired motor aptitude levels, while those with PD were more likely to have deficits in all areas than participants without PD, but mostly showed normal Perceptive aptitude. Although our findings were generally consistent with prior observations from other studies (Keloth et al, 2019;Lazarotto et al, 2020;Lee et al, 2018;Stegemöller et al, 2019;Stuart et al, 2019;Xu et al, 2018) our use of the MSOA permitted greater specification in describing motor aptitude differences of older adults with and without PD. Furthermore, participant gender and age group were associated with these motor aptitude outcomes, regardless of the presence or absence of PD.…”
Section: Discussionsupporting
confidence: 90%
“…Considering inherent age-related motor losses, it is important to specify the motor behavior of older adults with and without PD in order to distinguish motor deficits associated with PD (Lazarotto et al, 2020; Stuart et al, 2019). Most prior studies comparing motor skills in individuals with and without PD have evaluated gait elements (Keloth et al, 2019; Xu et al, 2018), postural control (Lazarotto et al, 2020), and manual dexterity (Lee et al, 2018; Stegemöller et al, 2019), with further research comparing multiple motor skills between these two groups limited.…”
Section: Introductionmentioning
confidence: 99%
“…PD patients also experience significant disability from impaired manual dexterity, which causes difficulty with tasks like tying shoelaces, fastening buttons, and handwriting (Pohar & Allyson Jones, 2009). This symptom is distinct from bradykinesia (Foki et al, 2016), but also responds to dopamine replacement (Gebhardt et al, 2008, Lee et al, 2018. Thus, dopamine plays an important, but poorly defined, role in dexterous skill beyond simply regulating movement speed or amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…However, PD patients also experience significant disability from impaired manual dexterity, which causes difficulty with tasks like tying shoelaces, fastening buttons, and handwriting (Pohar & Allyson Jones, 2009). This symptom is distinct from bradykinesia (Foki et al, 2016), but also responds to dopamine replacement (Gebhardt et al, 2008, Lee et al, 2018). Thus, dopamine plays an important, but poorly defined, role in dexterous skill beyond simply regulating movement speed or amplitude.…”
Section: Introductionmentioning
confidence: 99%